GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 14313 species occurrences available in GBIF matching the query: TaxonKey: Watsonalla binaria Hüfnagel, 1769. The dataset includes 14313 records from 54 constituent datasets: 12 records from Merseyside BioBank (unverified). 8 records from International Barcode of Life project (iBOL). 9 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 4 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 4 records from Lund Museum of Zoology - Insect collections (MZLU). 4 records from Entomology, Natural History Museum, University of Oslo. 768 records from Artdata. 4 records from Données ONF Faune-Flore-Fonge. 1 records from Norwegian Biodiversity Information Centre - Other datasets. 5 records from iNaturalist Research-grade Observations. 11 records from Estonian Museum of Natural History. 22 records from Estonian University of Life Sciences. 14 records from Collection entomologique Barthélémy. 1 records from FFH-Gebiet "Calwer Heckengäu". 164 records from naturgucker. 137 records from Natural History Museum Rotterdam (NL) - Lepidoptera observations. 69 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 10 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 32 records from Natural History Museum Maastricht (NL) - Entomological Collection. 68 records from Insekten Sachsen. 1 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 2031 records from Data on moths from automatically operating light traps in Denmark. 1 records from Norwegian Lepidoptera working group. 62 records from BRERC species records recorded over 15 years ago. 1 records from Natural History Museum (London) Collection Specimens. 2 records from NMNH Extant Specimen and Observation Records. 1 records from European Lepidoptera Observations by Donald Hobern. 169 records from Lepidoptera collection of Hannu Saarenmaa. 2 records from Biologiezentrum Linz. 75 records from inatura - Erlebnis Naturschau Dornbirn. 59 records from European Moth Nights. 1 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 6671 records from Bugbase, Lepidopterological Society. 56 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 4 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 328 records from Biological and palaeontological collection and observation data MNHNL. 1 records from English Nature Oxfordshire Invertebrate Surveys. 5 records from Finnish Entomological Database: Lepidoptera. 1 records from National Trust - Ickworth species data held by The National Trust.. 5 records from Geographically tagged INSDC sequences. 11 records from Norwegian Species Observation Service. 320 records from Staffordshire Ecological Record - SER Species-based Surveys. 8 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 4 records from Données ONF Faune-Flore-FOnge. 45 records from Natural History Museum Rotterdam (NL) - Insecta collection. 15 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 1710 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 6 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1247 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 19 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 102 records from BRERC species records within last 15 years. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences